PERAWATAN PERIANAL DENGAN BABY OIL MENURUNKAN KEJADIAN DIAPER DERMATITIS PADA NEONATUS DI RUANG NEONATUS RSUD SIDOARJO - Umamah, Farida; Chasanah, Navi Fitrothul (Jurnal Ilmiah Kesehatan (Journal of Health Sciences), 2013)
The Influence of Perianal Care with Baby Oil in Order to Prevent Diaper Dermatitis on Neonates in Neonates Room of RSUD Sidoarjo. The purpose of this research is to know the effect of perianal  care with baby oil in order to prevent diaper dermatitis on neonates in neonates room of RSUD Sidoarjo. Quasy experiment was used in designing this study. The population were all babies hospitalized in neonates room of RSUD Sidoarjo. Size of sample was 20 respondents fulflling inclusion criteria. Sample is collected by using purposive sampling technique. Independent variable in this research was the method of perianal care with baby oil and dependent variable was incidence of diaper dermatitis in neonates. Used instrument is check list and structured observation. Then the data was analyzed by using Mann Whitney statistic test. From the research, all pretest score is good both on experiment group and control group with condition of normal skin is 100%. Meanwhile posttest score on experiment group with condition of normal skin is 90% and on control group with condition of normal skin is 50% but almost a half of them (40%) suffer mild diaper dermatitis. From the result of statistic test it shows that r = 0,045 < a = 0,05. The conclusion of this research is that routine perianal care with baby oil before wearing diaper after urination and defecation is effective to prevent diaper dermatitis incident in neonates. To prevent diaper dermatitis can be done with perianal care use baby oil routinely.